Interventions for the control of Aedes aegypti in Latin America and the Caribbean: systematic review and meta-analysis - Bardach, Ariel Esteban (2019)
Objective: To determine the effectiveness and degree of implementation of interventions for the control of Aedes aegypti in Latin America and the Caribbean (LAC) as reported in scientific literature. Methods: We searched MEDLINE, EMBASE, CENTRAL, SOCINDEX, and LILACS, for experimental and observational studies, economic assessments and qualitative experiences carried out in LAC from 2000 to 2016. We assessed incidence and morbimortality of Aedes aegypti-related diseases and entomological indices: Breteau (containers), House, and Pupae per Person. We used GRADE methodology for assessing quality of evidence. Results: Of 1826 records retrieved, 75 were included and 9 cluster randomised clinical trials could be meta-analysed. We did not identify any intervention supported by a high certainty of evidence. In consistency with qualitative evidence, health education and community engagement probably reduces the entomological indices, as do the use of insecticide-treated materials, indoor residual spraying and the management of containers. There is low certainty of evidence supporting the use of ovitraps or larvitraps, and the integrated epidemiological surveillance strategy to improve indices and reduce the incidence of dengue. The reported degree of implementation of these vector control interventions was variable and most did not extend to whole cities and were not sustained beyond 2 years. Conclusions: We found a general lack of evidence on effectiveness of vector control in the region, despite a few interventions that showed moderate to low certainty of evidence. It is important to engage and educate the community, apart from achieving the implementation of integrated actions between the health and other sectors at national and regional level.